MONOPOLI BADAN USAHA MILIK NEGARA (BUMN) PADA PENGATURAN PENUMPUKAN PETIKEMAS DI PELABUHAN L. SAY MAUMERE SEBAGAI PELABUHAN MULTIPURPOSE(Studi Putusan Nomor 15/Kppu-L/2018) - Ahamd Rosyadi (2021)
This research is to examine the legal decision made by the Business Competition Supervisory Commission on PT. Pelindo III related to the monopoly of 100% stack arrangement at L. Say Maumere Port where L. Say Maumere Port is a Multipurpose Port. The results of the study found that PT. Pelindo III as a State-Owned Enterprise carries out a monopoly practice which results in an increase in prices for loading and unloading at the Port of L. Say Maumere. The problem is that the L.Say Maumere Port, which incidentally is a Multipurpose Port, is not allowed to load and unload with a 100% stack system. The research method was carried out in a normative juridical manner with data from court decisions, literature books and related journals. The results of the study concluded that PT. Pelindo III carried out a monopoly related to stack 100% which was carried out at the Port of L. Say Maumere as a Multipurpose Port. Keywords: BUMN Monopoly, PT. Pelindo III